2017
DOI: 10.5539/hes.v7n3p148
|View full text |Cite
|
Sign up to set email alerts
|

Relating the Learned Knowledge and Acquired Skills to Real Life: Function Sample

Abstract: Considering that Mathematics is a multidimensional problem-solving method that can be effective in all areas of cultural life, it is of great importance because of its contribution to other sciences such as physical and social sciences. It is known that the basic concepts of mathematics, which can also be expressed as a way of life, have helped to increase the usefulness of mathematics to practical and even social sciences such as physics, chemistry, biology, economics, engineering and military, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The student who could not analyze anything for the first time was able to start reasoning about being rotationally symmetric after looking at examples from daily life. It was concluded that the student was motivated by everyday life examples (Albayrak et al, 2017). Another important finding in this study is that using daily life examples while examining rotational symmetry strengthens students' ability to make connections between concepts by strengthening their abstraction mechanisms of the concept of rotational symmetry (Doruk & Çiltaş, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…The student who could not analyze anything for the first time was able to start reasoning about being rotationally symmetric after looking at examples from daily life. It was concluded that the student was motivated by everyday life examples (Albayrak et al, 2017). Another important finding in this study is that using daily life examples while examining rotational symmetry strengthens students' ability to make connections between concepts by strengthening their abstraction mechanisms of the concept of rotational symmetry (Doruk & Çiltaş, 2020).…”
Section: Discussionmentioning
confidence: 77%